1998
DOI: 10.1095/biolreprod59.5.1037
|View full text |Cite
|
Sign up to set email alerts
|

Relative Impact of Oxidative Stress on the Functional Competence and Genomic Integrity of Human Spermatozoa1

Abstract: Reactive oxygen metabolites are known to disrupt sperm-oocyte fusion, sperm movement, and DNA integrity; however, the relative sensitivities of these elements to oxidative stress are unknown. In this study these factors were assessed in human spermatozoa exposed to increasing levels of oxidative stress achieved through the stimulation of endogenous oxidant generation with NADPH or direct exposure to hydrogen peroxide. At low levels of oxidative stress, DNA fragmentation was significantly reduced while the rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
342
0
26

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 686 publications
(387 citation statements)
references
References 48 publications
19
342
0
26
Order By: Relevance
“…The mechanisms of DNA damage in human spermatozoa include defective sperm chromatin packing, apoptosis and oxidative stress [3][4][5]. Protamine has a critical role in spermatid differentiation; protamine deficiency can lead to sperm DNA damage and embryonic death in mice [6].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of DNA damage in human spermatozoa include defective sperm chromatin packing, apoptosis and oxidative stress [3][4][5]. Protamine has a critical role in spermatid differentiation; protamine deficiency can lead to sperm DNA damage and embryonic death in mice [6].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro experiments in which spermatozoa were exposed to initiators of oxidative stress such as H 2 O 2 revealed a significant increase in DNA damage in the form of either single-and double-strand breaks or DNA modification products. [69][70][71] Our investigations have provided evidence showing that DNA fragmentation in human spermatozoa after in vitro exposure to H 2 O 2 could be prevented by the addition of exogenous gangliosides. Flow cytometric analyses revealed that the pre-treatment of spermatozoa with GT1b micelles almost completely abolished H 2 O 2 passage through the cell membrane ( Figure 4).…”
Section: Gangliosides and Spermatozoamentioning
confidence: 87%
“…Tests of DNA integrity are going to be an important part of the overall evaluation of male infertility as use of sperm with damaged DNA in ART has been linked with adverse clinical outcomes, including an increased risk of miscarriage and morbidity in the offspring, including childhood cancer [6,7]. However, DNA integrity test scores must be critically evaluated for utility in directing infertile couples to the 'best' ART keeping in mind that there is a significant increased risk of birth defects in the offspring from couples who had successful ICSI attempts at pregnancy; a risk not found for the offspring from couples with successful IUI, and/or IVF-ET attempts at pregnancy [19].…”
Section: Discussionmentioning
confidence: 99%
“…The 9 patients with failed ICSI cycles should be evaluated for exposure to agents known to negatively affect male reproductive health by having these patients review a list of the common agents known to negatively affect fertility including, medications, recreational drugs, alcohol, oxidative stress, cigarette smoking, environmental toxins, and even use of cell phones [1,2,[4][5][6][7]50]. If possible, these patients should be removed from agents that they identify may be causing their infertility for 3 months, and then retested to see if their SDD Test score has improved.…”
Section: Treatment Options For Category 3 Couples (N010)mentioning
confidence: 99%
See 1 more Smart Citation